The effect of arsenic on mitochondrial fatty acid metabolism via inhibition of carnitine palmitoyltransferase 1B and choline kinase beta in C2C12 cells - Fu-Lin Yu; Ming-Yan Zhang; Gang-Wei Song; Yang-Shan Ning; Xian Wu; Yan Gao (PLoS ONE, 2025)
Arsenic can enter the human body through environmental exposure via food, drinking water, and chemotherapy for cancer. Prolonged and excessive exposure to arsenic causes various toxic reactions, leading to diseases that significantly impact health and lifespan. Increasing evidence suggests that arsenic damages skeletal muscle tissue by reducing muscle mass and causing atrophy, thereby contributing to conditions such as respiratory and cardiovascular diseases, as well as diabetes. Fatty acid β-oxidation is the most efficient mechanism for ATP production and serves as a primary energy source for tissues, including the heart and skeletal muscles. However, the metabolic mechanisms underlying arsenic’s effects on muscle function and pathogenesis remain incompletely understood. In this study, we investigated the role of mitochondrial fatty acid oxidation in arsenic-induced muscular damage using mouse skeletal muscle C2C12 cells. Our results demonstrated a dose-dependent inhibitory effect of sodium arsenite (0–2 µM, 72 hours) on C2C12 cells proliferation, viability, and differentiation (indicated by reduction of myogenic differentiation 1 mRNA expression). Arsenic exposure disrupted mitochondria through increasing reactive oxygen species production, reducing mitochondrial membrane potential to 16.45%, downregulating mitochondrial fatty acid metabolism-related enzymes (carnitine palmitoyltransferase 1B to 15.05% and choline kinase beta mRNA to 49.94%), and decreasing mitochondrial DNA copy number to 42.08%. These findings suggest that arsenic-induced pathological changes in skeletal muscle are associated with impaired mitochondrial membrane function, disrupted fatty acid metabolism, and reduced mitochondrial DNA content in muscle cells.